ANALISIS RESIDU PESTISIDA PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) DI KABUPATEN BREBES - Ubad Badrudin; Syakiroh Jazilah (LPPM Universitas Pekalongan, 2013)
The onion (Allium ascalonicum L.) is one of the horticultural crops that having a significant economic value. The center of onion production is in Brebes regency central of Java. It supplies about 50% nationaly need. The efforts of increased production of onion often faced constraints in the form of pests and diseases, thus failing to harvest crops or at least reduced. One way of action of plant maintenance is the use of pesticides. Pesticides are toxic chemicals, excessive use of pesticides can be a source of contaminants for food, water, and environment. The purpose of the study is determination of the type of pesticide applied, the frequency of spraying pesticides, and pesticide residues in onion crops in Brebes regency. The experiment was conducted in the Larangan subdistrict, Brebes district from June to November 2010. Onion crop’s samples were taken from the most extensive farmers as much as 10% of whole villages in the subdistrict of Larangan, Brebes. Research methods by interviewing and laboratory analyzed by gas of chromatography (GC). The observed variables include the type of pesticide applied, the frequency of use of pesticides, and pesticide residues in onion crop. The analysis data made by way of recapitulation, described and compared with maximum residue limits of pesticides in accordance with the Joint Degree of the Ministry of Agriculture and Ministry of Health, No. 881/MENKES/SKB/VIII/1996; 711/Kpts/TP.270/8/1996. The results showed that the type of pesticide that was applied to the onion plant consists of several kinds of pesticides, with an average frequency of spraying fifteen times in one planting season, while the pesticide of residues in onion crop is below the maximum residue limits (MRL), so that it is still relatively safe for consumption.Keywords: Pesticide of residues, Onion, Brebes